Digital Pragmatics and Human Identity in Interactions With Select Ai Chatbots - Chukwuma Livinus Ndububa; Bibian Ugoala (Prodi Ilmu Komunikasi UTM, 2025)
In today’s digital world, Artificial Intelligence (AI) chatbots play a major role in transforming human identity. People engage with digital platforms for different reasons; in doing so, the experiences they have and the interactive nature of the digital platforms seem to influence them, since human beings are products of their thoughts and surroundings. Based on this background, this study looks at how interacting with selected language models affects people’s self-image and digital communication. Grounded in pragmatic theory with a focus on Sperber and Wilson’s Relevance Theory (1995), the study aims to analyze how AI chatbots like ChatGPT, Copilot, and Gemini adapt to users’ identities, tones, and communicative intentions; and to examine how digital pragmatics shapes or reinforces users’ self-perception and identity expression in conversations with these models. After reviewing existing literature and identifying gaps, the study adopted a pre-experimental, comparative qualitative method, analyzing 33 chat screenshots—11 from each chatbot. The data were purposively grouped into nine themes. Findings showed, among other things, that ChatGPT and Copilot are more culturally adaptable than Gemini which struggles to respond to certain identity cues. ChatGPT stands out in recognizing communicative intent and stated identity, while Copilot offers the warmest and most cordial interactions. Overall, human identity is influenced—consciously or not—by frequent interaction with these language models. The study, therefore, urges caution in how often and in what ways users engage with these impassive AI systems. It concludes that digital tools can reshape self-image and human identity, and offers insights that are valuable not only to scholars of language and communication, but also to anyone interested in how digital pragmatics shapes both our sense of self and our perception of human existence.